Divergent evolution of temozolomide resistance in glioblastoma stem cells is reflected in extracellular vesicles and coupled with radiosensitization. Issue 2 (28th July 2017) - Garnier, Delphine; Meehan, Brian; Kislinger, Thomas; Daniel, Paul; Sinha, Ankit; Abdulkarim, Bassam; Nakano, Ichiro; Rak, Janusz
Abstract: Background: Glioblastoma (GBM) is almost invariably fatal due to failure of standard therapy. The relapse of GBM following surgery, radiation, and systemic temozolomide (TMZ) is attributed to the ability of glioma stem cells (GSCs) to survive, evolve, and repopulate the tumor mass, events on which therapy exerts a poorly understood influence. Methods: Here we explore the molecular and cellular evolution of TMZ resistance as it emerges in vivo (xenograft models) in a series of human GSCs with either proneural (PN) or mesenchymal (MES) molecular characteristics. Results: We observed that the initial response of GSC-initiated intracranial xenografts to TMZ is eventually replaced by refractory growth pattern. Individual tumors derived from the same isogenic GSC line expressed divergent and complex profiles of TMZ resistance markers, with a minor representation of O 6 -methylguanine DNA methyltransferase (MGMT) upregulation. In several independent TMZ-resistant tumors originating from MES GSCs we observed a consistent diminution of mesenchymal features, which persisted in cell culture and correlated with increased expression of Nestin, decline in transglutaminase 2 and sensitivity to radiation. The corresponding mRNA expression profiles reflective of TMZ resistance and stem cell phenotype were recapitulated in the transcriptome of exosome-like extracellular vesicles (EVs) released by GSCs into the culture medium. Conclusions: Intrinsic changes in the tumor-initiating cell compartment may include loss of subtype characteristics and reciprocal alterations in sensitivity to chemo- and radiation therapy. These observations suggest that exploiting therapy-induced changes in the GSC phenotype and alternating cycles of therapy may be explored to improve GBM outcomes.